1963
DOI: 10.1002/j.2164-4918.1963.tb04362.x
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction Researches of 1962

Abstract: This is the twenty‐first in a series. It covers reports published in 1962, plus earlier reports which have just come to the attention of the writers. Earlier summaries will be found in Job Satisfaction by Robert Hoppock (Harper & Bros., 1935) and in the following issues of Occupations: April, 1938; October, 1940; February, 1943; April, 1945; April, 1948; December, 1948; December, 1949; October, 1950; May, 1951; May, 1952. More recent summaries will be found in the following issues of the Personnel and Guidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1964
1964
1970
1970

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Job satisfaction studies in many different settings have suggested factors which appear to influence and enter into job satisfaction as a variable of work adjustment (Robinson & Conners, 1962, 1963 and (Scott, et al, 1958). Among others, whether or not a measure of overall job satisfaction or a measure of satisfaction with specific jobrelated factors is used appears to make a difference.…”
Section: Resultsmentioning
confidence: 99%
“…Job satisfaction studies in many different settings have suggested factors which appear to influence and enter into job satisfaction as a variable of work adjustment (Robinson & Conners, 1962, 1963 and (Scott, et al, 1958). Among others, whether or not a measure of overall job satisfaction or a measure of satisfaction with specific jobrelated factors is used appears to make a difference.…”
Section: Resultsmentioning
confidence: 99%